Efficiency of Investment Project Evaluation in the Development of Innovative Industrial Activities - Shaturaev, Jakhongir (Universitas Pendidikan Indonesia (UPI), 2023)
The article discusses the issues of the effectiveness of investment projects, and their assessment when introducing innovations into the process. As you know, innovations, both domestic and foreign, allow you to first create the prerequisites for stabilizing the situation in the country's economy, and then for a radical increase in its efficiency. That is why the theoretical substantiation of the conceptual approach, the development of practical recommendations for solving problems, and strategies for the innovative development of industries are becoming an important factor in progress and, therefore, very relevant and significant research for practice. The efficiency of investment projects is analyzed based on the goals of the industry, methods are used and a calculation is given to increase the efficiency of implemented projects in the industry. In this regard, it is necessary to note the particular importance of timely identification and systematic use of reserves for the implementation of innovative activities, as well as for increasing innovative activity to achieve more efficient further activities of industries.